2023
DOI: 10.1249/fit.0000000000000878
|View full text |Cite
|
Sign up to set email alerts
|

Can Boxing Deliver a Knockout Punch against Parkinson's Disease? A Review of the Evidence

Brooke Lowery,
Jennifer Flewwellin,
Sara Lynn Terrell

Abstract: Boxing is an exercise intervention for Parkinson's disease that is rising in popularity. Some research has demonstrated that boxing may improve gait, agility, balance, and quality of life in persons with Parkinson's disease. However, continued research is needed to fully discern the benefits of boxing in comparison with other exercise modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The present findings are partially in line with the systematic review of Morris et al [12] and the review of Lowery et al [22], who reported limited improvement in the mobility and quality of life of people with PD after the implementation of community boxing exercise programs, pointing out that the efficacy of these programs is limited. The above researchers stated that the limited evidence may be due to the small number of participants and the restricted number of randomized controlled trials up to date.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The present findings are partially in line with the systematic review of Morris et al [12] and the review of Lowery et al [22], who reported limited improvement in the mobility and quality of life of people with PD after the implementation of community boxing exercise programs, pointing out that the efficacy of these programs is limited. The above researchers stated that the limited evidence may be due to the small number of participants and the restricted number of randomized controlled trials up to date.…”
Section: Discussionsupporting
confidence: 91%
“…Another barrier may be the severity of the disease, which may be a major obstacle for participation. According to researchers [22], only patients at H&Y stages 1-3 may successfully participate. On the other hand, facilitators for participation may include the community nature of the activity that promotes the development of relationships between participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations